Strategi Penciptaan Humor dengan Pemanfaatan Aspek-aspek Kebahasaan - Muhammad Rohmadi (Humaniora, 2010)
Humor is universal. Nobody never gets involved with humor. It's the difference lies in its frequency and its target. One person may have a high sense of humor whereas another may have a low sense of humor. In fact every person needs humor in many communication activities. Though humor is only word game, people cannot avoid it. However, humor does not always cause the people to laugh. The creation of humor discourse can make use of articles, pictures, and sounds. Humor consumers assess humor variously. Sometimes people can feel happy when they hear humor; but sometimes they can feel infuriated, hateful, insinuated, or even aggrieved. This is caused by immeasurable humor context in each communication. It depends on the target that the humor creator wants.